1988
DOI: 10.1097/00006842-198801000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of insomniacsʼ MMPI profiles: relation of subtypes to sleep history and treatment outcome.

Abstract: The Minnesota Multiphasic Personality Inventory (MMPI) profiles of 100 insomniacs who presented for treatment at a university medical center were analyzed by a hierarchical clustering procedure. This analysis revealed two major personality types that accounted for 88% of the sample. The two types referred to as "Type 1" and "Type 2" insomniacs differed significantly in regard to sleep history questionnaire responses and responsivity to treatment. MMPI scales and sleep history questionnaire items suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 16 publications
2
42
0
3
Order By: Relevance
“…Relationships between insomnia and anxiety and depression have been reported in the clinical outcome literature. Edinger and colleagues, 60 for example, found that lower levels of anxiety were characteristic of older insomniacs who, in turn, showed a more positive treatment response, while in the epidemiological literature lower levels of depression have been associated with longer-term insomnia remission. 61 Negative results in the present analyses also merit attention.…”
Section: Outcome Variationsmentioning
confidence: 99%
“…Relationships between insomnia and anxiety and depression have been reported in the clinical outcome literature. Edinger and colleagues, 60 for example, found that lower levels of anxiety were characteristic of older insomniacs who, in turn, showed a more positive treatment response, while in the epidemiological literature lower levels of depression have been associated with longer-term insomnia remission. 61 Negative results in the present analyses also merit attention.…”
Section: Outcome Variationsmentioning
confidence: 99%
“…Several research groups have focused on identifying potential factors, which may predict treatment outcome in a bid to guide clinicians when selecting the most suitable treatment for their patient [20,21]. Characteristics such as the age of the patient [22][23][24] and the severity [11,25,26] and duration [25] of their insomnia have been recognized as predictors of treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has indicated that older participants had a poorer treatment response relative to younger participants [22,25], though insomnia severity and duration have not yet been consistently related to treatment outcome [21,23,25,26,41]. Dysfunctional beliefs and attitudes regarding sleep, sleep-related anxiety, and fatigue also were assessed as potential predictors of treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, none has explored other variables (e.g., personality, arousability) that may be involved in the etiology of insomnia in the general population. For instance, in clinical samples, the personality patterns of individuals with insomnia have been characterized by the presence of neurotic traits, inhibition of emotions, rumination, and inability to discharge anger outwardly [16][17][18][19][20]. Individuals with insomnia have also been described as having fewer adaptive coping skills, relying more on emotion-oriented coping strategies than problem-solving strategies, and reporting lower feelings of mastery [21][22][23].…”
Section: Introductionmentioning
confidence: 99%